2019
DOI: 10.1093/cercor/bhy345
|View full text |Cite
|
Sign up to set email alerts
|

Selective Modulation of Early Visual Cortical Activity by Movement Intention

Abstract: The primate visual system contains myriad feedback projections from higher- to lower-order cortical areas, an architecture that has been implicated in the top-down modulation of early visual areas during working memory and attention. Here we tested the hypothesis that these feedback projections also modulate early visual cortical activity during the planning of visually guided actions. We show, across three separate human functional magnetic resonance imaging (fMRI) studies involving object-directed movements,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 111 publications
(159 reference statements)
10
43
0
Order By: Relevance
“…In addition, previous fMRI studies report 1 5 networks in which preparatory neural activity preceding movement onset differentiates the limb to be used (Gallivan et al, 2013;Gallivan et al, 2015). Importantly, these fMRI studies report that during the planning phase, neural activity in sensory regions shows limb specificity (Gallivan et al, 2019). Thus, together with our results, there is sufficient evidence demonstrating that signals in visual cortex carry limb-specific information about motor commands during action planning and execution.…”
Section: Discussionsupporting
confidence: 81%
“…In addition, previous fMRI studies report 1 5 networks in which preparatory neural activity preceding movement onset differentiates the limb to be used (Gallivan et al, 2013;Gallivan et al, 2015). Importantly, these fMRI studies report that during the planning phase, neural activity in sensory regions shows limb specificity (Gallivan et al, 2019). Thus, together with our results, there is sufficient evidence demonstrating that signals in visual cortex carry limb-specific information about motor commands during action planning and execution.…”
Section: Discussionsupporting
confidence: 81%
“…The alpha band, suggested to play a role in cortico-cortical feedback processing 52 , was dominated by directed coherence emanating from the somatomotor cluster (Figure 4E), while a premotor cluster was the second strongest driver of alpha coherence. Together, these support the importance of motor-related regions in feedback processing 53,54 . We also noted that alpha coherence shifted from the dorsal visual cluster to the ventral visual cluster, in line with a top down flow from higher order to primary visual areas.…”
Section: Directed Information Processingsupporting
confidence: 59%
“…Similar strong modulations are now apparent during locomotion in the primary cortex of mice (Niell and Stryker, 2010). These complex effects can be generalized to the complete visual-motor loop: the execution of an action always generates a change in primary visual cortex (Gallivan et al, 2019;Gutteling et al, 2015;Monaco et al, 2020;Straube et al, 2017). Straube et al (2017) observed the suppression of the V1 BOLD response to visual stimulation caused by an action.…”
Section: Model Of the Bold Response Component Of The Visuo-motor Systemmentioning
confidence: 56%
“…Straube et al (2017) observed the suppression of the V1 BOLD response to visual stimulation caused by an action. This has been explained in the predictive code of the future consequence of the action (Brown et al, 2013;Gallivan et al, 2019;Rao and Ballard, 1999;Wolpert et al, 1995), also needed to elaborate a sense of agency. Our result reinforces the idea of temporal oscillation as a mechanism that mediates temporal binding, which is necessary both for predictive coding and for the sense of agency: they have the temporal precision to mediate binding and the great advantage to carry prediction.…”
Section: Model Of the Bold Response Component Of The Visuo-motor Systemmentioning
confidence: 99%